Structure-Function Relationships of Antimicrobial Peptides and Proteins with Respect to Contact Molecules on Pathogen Surfaces - Zhang, Ruiyan; Eckert, Thomas; Lutteke, Thomas; Hanstein, Stefan; Scheidig, Axel; M. J. J. Bonvin, Alexandre; E. Nifantiev, Nikolay; Kozar, Tibor; Schauer, Roland; Abdulaziz Enani, Mushira; Siebert, Hans-Christian (Current Topics in Medicinal Chemistry, 2016)
The Antimicrobial peptides (e.g. defensins, hevein-like molecules and food-protecting peptides like nisin) are able to interact specifically with contact structures on pathogen surfaces. Besides protein receptors, important recognition points for such contacts are provided by pathogen glycan chains or surface lipids. Therefore, structural data concerning surface exposed glycans and lipids are of the highest clinical interest since these recognition functions play a key role when optimising anti-infection therapies. Approaches in nanomedicine and nanopharmacology in which various biophysical techniques such as NMR (Nuclear Magnetic Resonance), AFM (Atomic Force Microscopy), SPR (Surface Plasmon Resonance) and X-ray crystallography can be combined with biochemical and cell-biological methods will lead to improved antimicrobial peptides by this rational drug design approach. Such a strategy is extremely well suited to support clinical studies focussing on an effective fight against multiresistant pathogens. The data sets which are described here can be considered as universal for the design of various antimicrobial drugs against certain pathogens (bacteria, viruses and fungi) which cause severe diseases in humans and animals. Furthermore, these insights are also helpful for progressing developments in the field of food conservation and food preservation. A detailed analysis of the structure-function relationships between antimicrobial peptides and contact molecules on pathogen surfaces at the sub-molecular level will lead to a higher degree of specificity of antimicrobial peptides.
Keywords: Nanopharmacology